Олександр Грушевський і становлення української архівістики у 1917–1920-ті роки - Приходько, Л. (Архіви України, 2008)
The article highlights O. Hrushevskyi’s many-sided heritage, in particular, his contribution to the development of Ukrainian studies and research, national history, historiography, source studies, historical geography, archival studies, ethnography, literature studies. Special emphasis is made on O. Hrushevskyi’s role with regard to the issues of Ukrainian archival studies, establishing the network of archival institutions, organizational activities on concentration, preservation, arrangement and use of archival documents.